Surgical removal of subfoveal perfluorocarbon liquid using combined 41 gauge needle and active aspiration under perfluorocarbon liquid (Annals of Medical Research, 2021)
A 57 years old patient underwent uneventfully 23-gauge pars plana vitrectomy (PPV) surgery containing perfluorocarbon liquid (PFCL) injection, endolaser retinopexy, fluid-air exchange, and silicone-oil implantation due to rhegmatogenous retinal detachment. The patient has admitted to the clinic due to decreased visual acuity caused by subfoveal retained PFCL detected with optical coherence tomography (OCT) 4 weeks after surgery. The patient underwent a reoperation to remove the residual subfoveal PFCL partially with a new technique.